ANALISIS FAKTOR SOSIAL EKONOMI YANG MEMPENGARUHI TINGKAT KRIMINALITAS DI SELURUH KABUPATEN/KOTA PROVINSI BALI TAHUN 2017-2021 - Jayanti, Samita; Yudha, I Made Endra Kartika (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 12 No 10 (2023): Vol.12.No.10. OKTOBER 2023[650-724], 2023)
Crime is a social problem that can disturb security and comfort in society. From 2017 to 2021 the crime rate that occurred in Bali Province shows a downward trend, but this figure is still relatively high. The purpose of this study is to analyze the simultaneous and partial effects of education, unemployment, poverty, per capita income, number of police, and pandemic on crime rates in districts/cities of Bali Province. This study uses secondary data collected from the Bali Regional Police and the Bali Province Central Statistics Agency (BPS). The analysis technique in this study is using panel data regression which produces the best model, namely the Fixed Effect Model (FEM). The results of this study indicate that 1) simultaneously the variables of education, unemployment, poverty, per capita income, the number of police, and the dummy pandemic affect the crime rate in the districts/cities of the Province of Bali; 2) partially the variables of education, per capita income, and the pandemic dummy have an effect on the crime rate in the districts/cities of Bali province, while the variables of unemployment, poverty, and the number of police officers have no effect on the crime rate in the districts/cities of the province of Bali. Keywords: Crime, Education, Unemployment, Poverty, Per Capita Income, Number of Police, and Pandemic.?